Further Study on the esterase patterns of sibling species in the Drosophila saltans subgroup (saltans group): Intraspecific and interspecific variations in the development - Nascimento, Adriana Pasqueto; De Bicudo, Hermione Elly Melara Campos (Springer Nature, 2006)
Twenty of the 32 esterase bands previously detected in the adults of D. prosaltans, D. saltans and D. austrosaltans were found in larvae and pupae studied in this work. The results showed that, in addition to expressing the highest number of esterase bands, the adult stage of the three species exhibited the highest degree of expression (amount of synthesis) for most of the bands. Differences between larval and pupal stages were detected in the degree of expression (amount of synthesis) of the bands and in the frequency of samples expressing them. The frequencies of expression of the bands corresponding to genes in loci 1-3 were greater in pupae than in larvae while the frequencies of expression of the bands corresponding to genes in loci 4-9 were predominantly expressed in larvae or were equal in both developmental stages. Like the adults, larvae, pupae and empty pupal cases (which were also studied in this work) showed specific esterases. Taken together, the observations showed that, in the species studied, every developmental stage is characterized by specific bands and by specific frequency and degree of expression of the bands shared with other stages. © Springer 2006.
Keywords: Drosophila; Esterase activity; Esterase patterns; Stage-specific esterases